PENGEMBANGAN PEMBELAJARAN DENGAN PEMBERIAN BALIKAN TERHADAP HASIL BELAJAR IPS SISWA - Najamuddin, M. (Jurnal Paedagogy, 2020)
This study aims to determine the application of learning development by giving feedback to the social studies learning outcomes of Class V at SDN 1 Praya Tengah. This research is an action research, because the research is conducted to solve learning problems in class. This research also includes descriptive research, because it describes how a learning technique is applied and how the desired results can be achieved. The data needed in this study were obtained through observations of the teaching and learning process using the feedback method and formative tests. and the interview method as a complementary method. This research uses descriptive analysis techniques with the Product Moment formula. Through the results of this study it shows that guided discovery learning has a positive impact in increasing student learning achievement, this can be seen from the increasingly stable students’ understanding of the material presented by the teacher (learning completeness increases from cycles I, II, and III), namely 68 , 18%, 77.27%, and 86.36%. In the third cycle, classical student learning completeness has been achieved. The conclusion of this study is that there is an effect of Learning Development with Giving Feedback on Social Studies Learning Outcomes of Class V at SDN 1 Praya Tengah.